EDUCATION CITY POLICY IN HANDLING CHILDREN WITHOUT SCHOOL - Bela Safira; Eri Yusnita Arvianti; Cahyo Sasmito (Awang Long Law Review, 2023)
The purpose of this research is to find out and analyze government policies as well as supporting and inhibiting factors to minimize children who do not go to school. The method in this research is qualitative research that focuses on city education policies. Data collection techniques with interviews, observation and documentation. and Conclusion The results of the study show that the government has a program to prevent children from dropping out of school, namely free elementary-junior high schools, a zoning system for new schools. students, free uniforms for underprivileged people, package A, B and C systems, and school buses. However, the fact is that the programs implemented have not been on target and there are still children who drop out of school in Malang City or the City of Education.